An In-Person and Telemedicine "Hybrid" System to Improve Cross-Border Critical Care in COVID-19 - Venktesh R. Ramnath; Linda Hill; Jim Schultz; Jess Mandel; Andres Smith; Tim Morris; Stacy Holberg; Lucy E. Horton; Atul Malhotra; Lawrence S. Friedman (Ubiquity Press, 2021)
Background:UC San Diego Health System (UCSDHS) is an academic medical center and integrated care network in the US-Mexico border area of California contiguous to the Mexican Northern Baja region. The COVID-19 pandemic deeply influenced UCSDHS activities as new public health challenges increasingly related to high population density, cross-border traffic, economic disparities, and interconnectedness between cross-border communities, which accelerated development of clinical collaborations between UCSDHS and several border community hospitals - one in the US, two in Mexico - as high volumes of severely ill patients overwhelmed hospitals. Objective:We describe the development, implementation, feasibility, and acceptance of a novel critical care support program in three community hospitals along the US-Mexico border. Methods:We created and instituted a hybrid critical care program involving: 1) in-person activities to perform needs assessments of equipment and supplies and hands-on training and education, and 2) creation of a telemedicine-based (Tele-ICU) service for direct patient management and/or consultative, education-based experiences. We collected performance metrics surrounding adherence to evidence-based practices and staff perceptions of critical care delivery. Findings:In-person intervention phase identified and filled gaps in equipment and supplies, and Tele-ICU program promoted adherence to evidence-based practices and improved staff confidence in caring for critically ill COVID-19 patients at each hospital. Conclusion:A collaborative, hybrid critical care program across academic and community centers is feasible and effective to address cross-cultural public health emergencies.